Auditoría Interna De La Información Contable Del Resguardo Indigena La Gaitana Del Municipio De Inzá Cauca (2025)
The purpose of this research work was to evaluate the conformity of the accounting information of the Indigenous Reservation la Gaitana de Inzá del Cauca with the International Financial Reporting Standards (IFRS) and to propose improvements that promote transparency and accounting organization through the analysis of the audit. The methodology used was of mixed approach, with descriptive and evaluative research, structured in phases: diagnosis of current regulations, collection and evaluation of information, analysis of the accounting software and creation of an improvement plan. The instruments included interviews with leaders of the safekeeping, documentary review and comparative analysis of software.